Investigating nonlinear speculation in cattle, corn, and hog futures markets using logistic smooth transition regression models - Andreas Röthig; Carl Chiarella (Technische Universität Darmstadt, Department of Law and Economics, 2006)
This article explores nonlinearities in the response of speculators' trading activity to price changes in live cattle, corn, and lean hog futures markets. Analyzing weekly data from March 4, 1997 to December 27, 2005, we reject linearity in all of these markets. Using smooth transition regression models, we find a similar structure of nonlinearities with regard to the number of different regimes, the choice of the transition variable, and the value at which the transition occurs.
Keywords: G10; G11; C22; C53; 330; Futures markets; speculation; nonlinear dynamics; smooth transition regression model; Spekulation; Anlageverhalten; Rohstoff-Futures; Schätzung; Australien